Evaluation of criminal responsibility - Packer, Ira K. (Best practices in forensic mental health assessment, 2009)
The legal context -- Forensic mental health concepts-- Empirical foundations and limits -- Preparation for the evaluation -- Data collection -- Interpretation -- Report writing and testimony